An introduction to orthodontics - Mitchell, Laura (New York : Oxford University Press, 2013)
Providing an introduction to current thinking and practice in orthodontics, this text covers all aspects of the field, including clinical practice and treatment planning.
1. The rationale for orthodontic treatment -- 2. The aetiology and classification of malocclusion -- 3. Management of the developing dentation -- 4. Craniofacial growth, the cellular basis of tooth movement and anchorage -- 5. Orthodontic assessment -- 6. Cephalometrics -- 7. Treatment planning -- 8. Class I -- 9. Class II division 1 -- 10. Class II division 2 -- 11. Class III -- 12. Anterior open bite and posterior open bite -- 13. Crossbites -- 14. Canines -- 15. Anchorage planning -- 16. Retention -- 17. Removable appliances -- 18. Fixed appliances -- 19. Functional appliances -- 20. Adult orthodontics -- 21. Orthodontics and orthognathic surgery -- 22. Cleft lip and palate and other craniofacial anomalies -- 23. Orthodontic first aid
Includes bibliographical references and index
Keywords: Orthodontics; Orthodontics -- Education